Analisis Faktor -Faktor yang Memengaruhi Kinerja Karyawan PT. Semen Indonesia Unit Tonasa di Kabupaten Pangkep - Multazam, Riana; Sahabuddin, Romansyah; Rahim, Abdul; Najamuddin, Najamuddin; Ramli, Anwar (J-MAS (Jurnal Manajemen dan Sains), 2024)
This study aims to evaluate the factors that impact employee performance at PT. Semen Indonesia Unit Tonasa, Pangkep Regency, using quantitative analysis methods and statistical techniques with the assistance of SPSS software. The data were obtained through the distribution of questionnaires to all employees, especially those in supervisory roles, with a total of 475 respondents. The results of the study indicate that work motivation, discipline, job commitment, organizational culture, and job compensation have a positive and significant influence on employee performance, both individually and collectively. The higher the levels of work motivation, discipline, job commitment, organizational culture, and job compensation, the higher the employee performance tends to be. These findings have important implications for company management in efforts to improve employee performance and address challenges arising from structural changes and the economic conditions of the company.